Anastomotic Revision in Head and Neck Free Flaps. (10th September 2020) - Stewart, Matthew; Swendseid, Brian; Hammond, Perry; Khatiwala, Ishani; Sarwary, Juliana; Zhan, Tingting; Heffelfinger, Ryan; Luginbuhl, Adam; Sweeny, Larissa; Wax, Mark K.; Curry, Joseph M.
Abstract : Objectives/Hypothesis: Predictors of free tissue transfer (FTT) failure and the need for postoperative revision (POR) have been extensively studied; however, there are little data evaluating outcomes when intraoperative revision (IOR) at initial surgery is required. This study seeks to better understand the impact IOR of the pedicle has on FTT outcomes. Study Design: Retrospective review of 2482 consecutive patients across three tertiary institutions. Methods: Adult patients (>18) who received a FTT and underwent anastomotic revision from 2006 to 2019 were included. Logistic regression was performed to predict revision, and recursive partitioning was performed to classify risk of failure based on type of revision and vessels revised. Results: Failure rates for IOR (19%) and POR (27%) were higher compared to a nonrevised failure rate of 2% ( P < .01 and P < .01, respectively). Intraoperative venous revision (IORv, n = 13), arterial (IORa, n = 114), and both (IORb, n = 11) were associated with failure rates of 8% (odds ratio [OR] 3.5, P = .23), 18% (OR = 9.0, P < .01), 45% (OR = 35.3, P = <.01), respectively. Arterial revision was most common among IOR (83%, P < .01). Postoperative venous revision (PORv, n = 35), arterial (PORa, n = 36), and both (PORb, n = 11) were associated with failure rates of 20% (OR = 15.7, P < .01), 27% (OR = 10.6, P < .01), and 39% (OR = 27.0, P < .01), respectively. Failure rate for flaps that had POR after IOR (PORi, n = 11) was 45% (OR = 18.2, P < .01). Diabetes predicted IOR ( P = .006); tobacco use, heavy alcohol use, and prior radiation predicted POR ( P = .01, P = .05, and P = .01, respectively). Conclusion: Both IOR and POR were associated with increased failure compared to nonrevised flaps. The risk of failure increases sequentially with intraoperative or POR of the vein, artery, or both vessels. Revision of both vessels and POR after IOR are strongly predictive of failure. Level of Evidence: 3 Laryngoscope, 131:1035–1041, 2021